CARACTERIZAÇÃO DE CULTIVARES DE PIMENTA BIQUINHO ADUBADO ORGANICAMENTE - CARDOSO, Reginaldo de Moraes; RAMIRES, Lucas Richard da Silva; VOLPATO, Tulio; MARCELINO, Adriele Ferreira; ALVES, Raisa Eduarda Lopes; SILVA, Maiele Leandro (ANAIS DO ENIC, 2018)
-